Association between poverty, low educational level and smoking with adolescent’s working memory: cross lagged analysis from longitudinal data - Nugroho, Hari Wahyu; Salimo, Harsono; Hartono, Hartono; Hakim, Moh Abdul; Probandari, Ari (Frontiers in Public Health, 2024)
Background Working memory is a crucial element of cognitive function. Previous cross-sectional studies have identified various determinants of working memory in children and adolescents. Nonetheless, no study has yet demonstrated the causal relationship of social determinants with working memory in adolescents. Objective This study explores the causal link between the level of education, smoking, and other factors with adolescent’s working memory. Methods This study analyzed secondary data from waves 4 and 5 of the Indonesia Family Life Survey (IFLS), utilizing cross-lagged analysis in Jamovi version 2.4.8. The variables included working memory score, maternal education, household income, stress, educational level, smoking, urbanicity, and physical activity. These variables were extracted from IFLS waves 4 and 5, and each dependent variable in IFLS wave four was controlled by the same dependent variables in IFLS 5. Then, we used cross-lagged analysis to assess the causality between each dependent variable and a working memory score in IFLS wave 5. Result The findings indicate that level of education had a positive impact on working memory in adolescents aged 15–18 years, with a Beta value of 0.18 (95% CI 0.81–0.2; p < 0.001). Smoking and age were negatively associated with working memory, with Beta values of −0.07 (95% CI -0.65 -0.04; p < 0.029) and − 0.10 (95% CI -0.25 -0.05; p < 0.003), respectively. No evidence was found for a significant correlation between poverty and adolescents’s working memory. Conclusion The findings indicate that increased education levels are associated with improved working memory in adolescents aged 15–18. At the same time, smoking has a negative impact on working memory in this age group.